Method for preparing mine ecological restoration structure layer material by phosphogypsum and carbon sequestration
Patent Information
- Application Number
- CN202611110331.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]针对现有技术中磷石膏基矿山生态修复材料普遍存在结构致密性不足、长期渗透稳定性差、CO2矿化效率低以及工业固废协同利用程度不高等技术问题,本发明提供了一种磷石膏协同碳封存制备矿山生态修复结构层材料的方法
1、工艺简单、原料绿色高效利用:以磷石膏、电石渣和粉煤灰为主要原料,无需高温煅烧或复杂化学改性处理,实现工业固废的大规模资源化利用;
Smart Images

Figure CN122977808A_ABST
Abstract
Description
Technical Field
[0001] This invention discloses a method for preparing structural layer materials for mine ecological restoration through phosphogypsum co-capture, which belongs to the field of industrial solid waste recycling. Background Technology
[0002] The continued development of industries such as phosphorus chemicals, thermal power generation, and metallurgy, while driving industrialization, not only releases large amounts of carbon dioxide (CO2) into the environment but also generates substantial industrial solid wastes such as phosphogypsum (PG), fly ash (FA), and calcium carbide slag (CS). The long-term accumulation of these solid wastes not only occupies significant land resources but also poses a potential pollution risk to surrounding soil and groundwater due to rainwater leaching and surface runoff, as pollutants such as phosphorus and fluorine are easily migrated. Simultaneously, the large amounts of carbon dioxide emitted during industrial production are a significant contributor to the greenhouse effect. Therefore, achieving the resource utilization of industrial solid waste and the co-fixation of carbon dioxide has become an important research direction for solid waste disposal and green, low-carbon development.
[0003] Mine ecological restoration is an important application area for the resource utilization of industrial solid waste. The structural layer of mine ecological restoration needs to perform functions such as slope support, seepage prevention, and vegetation restoration, while also possessing good durability and environmental safety. In engineering applications, restoration materials typically require high mechanical strength and resistance to rainwater erosion to ensure long-term slope stability; simultaneously, they must have excellent seepage prevention performance, with a permeability coefficient generally required to be no higher than 1×10⁻⁶. -7 The material's viscosity should be cm / s and should be maintained or further reduced over the extended maintenance period to effectively block pollutant migration. Furthermore, the material should meet the leaching toxicity requirements of GB 5085.6 and possess good air permeability and water retention properties to meet the needs of vegetation establishment and ecological restoration. In recent years, the preparation of mine restoration materials through mineralization carbon sequestration technology has received widespread attention. This technology utilizes carbon dioxide mineralization reactions to promote the formation of carbonate minerals within the material, achieving structural densification. While improving the material's mechanical properties, impermeability, and durability, it also achieves long-term stable carbon dioxide sequestration, combining the advantages of resource utilization and pollution reduction / carbon reduction.
[0004] Currently, materials for mine ecological restoration mainly include natural clay materials, cement-based cementitious materials, and industrial solid waste-based materials. While natural clay materials have a low permeability coefficient, they are susceptible to shrinkage and cracking due to wet-dry cycles, making long-term impermeability difficult to guarantee. Cement-based materials offer high mechanical strength, but their production process relies on cement clinker firing, resulting in high energy consumption and carbon emissions. Although industrial solid waste-based materials can improve the resource utilization level of industrial solid waste, most existing technologies still require the addition of cement, lime, or chemical additives, limiting solid waste utilization and increasing preparation costs, making it difficult to simultaneously achieve mechanical properties, impermeability, ecological safety, and low-carbon requirements. For example, invention application CN1170024102A discloses a phosphogypsum-based waterproof mortar and its preparation method, using calcined phosphogypsum as the main raw material and adding cement, slag, and lime to prepare the waterproof mortar; invention application CN111133395A discloses a high-strength, water-resistant phosphogypsum-based composite cementitious material, using phosphogypsum, cement, and lime powder as the main raw materials, and adding water-reducing agents and retarders to prepare the water-resistant material; invention application CN115215624A discloses a method for carbon dioxide geological sequestration using phosphogypsum, using anhydrous phosphogypsum, cement, and red mud as filling materials to achieve carbon dioxide sequestration. Although the above-mentioned prior art has achieved the resource utilization of phosphogypsum or carbon dioxide fixation, it generally suffers from problems such as dependence on cement or high-temperature calcination processes, high carbon emissions, large amounts of admixtures, limited solid waste content, and difficulty in synergistically optimizing material performance and carbon sequestration function. These limitations make it difficult to meet the comprehensive requirements of mine ecological restoration projects for high solid waste utilization, high performance, low carbonization, and large-scale application. Summary of the Invention
[0005] To address the common technical problems in existing phosphogypsum-based mine ecological restoration materials, such as insufficient structural density, poor long-term permeability stability, low CO2 mineralization efficiency, and low degree of co-utilization of industrial solid waste, this invention provides a method for preparing mine ecological restoration structural layer materials using phosphogypsum and co-capture carbon. This method uses phosphogypsum, carbide slag, and fly ash as main raw materials. Through the coupled regulation of raw material synergistic activation and CO2 mineralization maintenance, it achieves simultaneous high-value utilization of solid waste and carbon sequestration, thereby constructing a highly dense, low-permeability, and long-term stable mine ecological restoration structural layer material.
[0006] The method for preparing structural layer materials for mine ecological restoration using phosphogypsum and co-carbon sequestration according to the present invention is as follows: 1. Raw material pretreatment: After drying and removing impurities, the phosphogypsum raw material is crushed and screened to obtain phosphogypsum powder; the carbide slag and fly ash are crushed separately, and the particle size of the crushed fly ash and carbide slag is less than 200 mesh. 2. Solid waste co-mixing: The raw materials processed in step 1 are thoroughly mixed under dry conditions to obtain a homogeneous mixture; The raw materials are 35%–65% phosphogypsum, 11%–22% carbide slag, and 23%–40% fly ash by mass, with the mass ratio of carbide slag to fly ash being 1:2. 3. Aging treatment: Aging the mixture from step 2 at room temperature for 7-9 hours to achieve interparticle rearrangement and ion equilibrium; 4. Slurry preparation and molding: Water is added to the aged mixture to make a slurry, which is then molded under pressure and demolded to form the initial structural framework; the water-cement mass ratio is 0.45-0.55:1; 5. High humidity pre-curing: Cur the molded sample in a high humidity environment of 18-22℃ and relative humidity ≥95% for 24 hours; 6. CO2 mineralization curing: The samples are then transferred to a mineralization environment with a temperature of 18-22℃, a relative humidity of 55%-65%, and a carbon dioxide atmosphere for curing for more than 7 days to achieve secondary densification and long-term stabilization of the material.
[0007] The volume percentage of carbon dioxide in the carbon dioxide atmosphere is 20%.
[0008] The permeability coefficient of the mine ecological restoration structural layer material prepared by the method of this invention is no greater than 1.0 × 10⁻⁶ after 28 days. -7 It has a speed of cm / s and also has pollutant barrier properties.
[0009] The principle of this invention: By synergistically combining phosphogypsum, carbide slag, and fly ash, multi-source active components such as Ca, Si, and Al are introduced, releasing Ca under hydration conditions. 2+ The presence of active silica-alumina species provides a reaction basis for subsequent gelation reactions. During the high-humidity curing stage, moisture continuously participates in ion migration and hydration reactions within the system, gradually generating gelation products such as C-(A)-SH and constructing a continuous solid-phase framework. Simultaneously, it forms an initial porous structure with a certain degree of connectivity, providing mass transfer channels for gas diffusion and subsequent mineralization reactions. Then, external CO2 dissolves under suitable humidity conditions to form a carbonic acid system, reacting with free Ca(OH)2 and active Ca in the system. 2+ Carbonization reaction occurs to generate CaCO3 sedimentary phase, which, together with hydration products, fills the pore structure, thereby achieving stepwise pore closure and continuous densification of the structure.
[0010] In the above process, hydration reaction provides the structural framework, porous structure provides mass transfer channels, and CO2 mineralization achieves secondary filling and enhanced densification. The three work together to construct a low-permeability and high-stability structural layer material system for mine ecological restoration.
[0011] The beneficial effects of this invention are as follows: 1. Simple process and green and efficient utilization of raw materials: Using phosphogypsum, carbide slag and fly ash as the main raw materials, no high-temperature calcination or complex chemical modification treatment is required, realizing large-scale resource utilization of industrial solid waste. 2. Significantly improved structural compactness: Through the synergistic effect of hydration reaction and CO2 mineralization, the internal pores of the system are continuously filled by C-(A)-SH gel and CaCO3, which significantly reduces the connectivity of permeation channels and improves structural integrity; 3. Synergistic achievement of carbon sequestration and ecological restoration: CO2 is continuously solidified into stable carbonates during the mineralization and maintenance process, achieving a synergistic unity between carbon emission reduction and material performance improvement; 4. Excellent long-term stability and low permeability: The formed composite cementitious-carbonate dual skeleton structure effectively improves the material's impermeability and resistance to environmental erosion, which can meet the engineering needs of mine slope restoration, tailings dam seepage prevention and pollution barrier; it can be used for mine slope restoration, tailings dam seepage prevention, abandoned mine pit treatment, contaminated site barrier layer or other mine ecological restoration projects. Attached Figure Description
[0012] Figure 1 This is a comparison of the flexural strength of materials prepared at different carbonization ages for Examples 1-7 (Figure a) and Comparative Examples 1-7 (Figure b); Figure 2 Figure 1-7 (a) and Figure 1-7 (b) are comparison diagrams showing the compressive strength of materials prepared at different carbonization ages. Figure 3 Comparative figures 8-9 show the strength at different ages (where a is the flexural strength and b is the compressive strength). Figure 4 This is a comparison chart of the permeability coefficients of the materials prepared in Examples 1-7 and Comparative Examples 1-7 after a carbonization period of 3 days; Figure 5 Comparison of permeability coefficients of materials prepared in Examples 1-7 and Comparative Examples 1-7 at a carbonization age of 7 days; Figure 6 This is a comparison chart of the permeability coefficients of the materials prepared in Examples 1-7 and Comparative Examples 1-7 after a carbonization period of 14 days; Figure 7 This is a comparison chart of the permeability coefficients of the materials prepared in Examples 1-7 and Comparative Examples 1-7 after a carbonization period of 28 days; Figure 8 This is a graph showing the change in permeability coefficient at different ages for comparative examples 8-9. Figure 9 The infrared spectrum (a) and XRD test pattern (b) of the materials prepared in Examples 2-4 and Comparative Examples 2-4 of this invention are shown. Detailed Implementation
[0013] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, the scope of protection of the present invention is not limited to the contents described. Unless otherwise specified, the reagents and methods used in the embodiments are all conventional reagents and conventional methods. In the following examples, the phosphogypsum was sourced from Yuntianhua Group, and its main components were CaO 40.305%, SiO2 6.799%, and Al2O3 0.4069%; the carbide slag was sourced from Weifang, Shandong, and its main components were CaO 89.4%, SiO2 2.92%, and Al2O3 1.58%; and the fly ash was sourced from Hubei Jingbangda Co., Ltd., and its main components were CaO 5.5%, SiO2 49.33%, and Al2O3 28.62%.
[0014] In the following examples, the compressive strength, flexural strength, permeability coefficient, and toxicity leaching tests of the materials were conducted according to the determination standards in Table 1. Table 1 Measurement Standards
[0015] Example 1: A method for preparing structural layer materials for mine ecological restoration using phosphogypsum and co-capture carbon. S1. Pretreatment: Dry the phosphogypsum at 80℃ for 24 hours to remove free moisture and volatile impurities, crush it and pass it through an 80-mesh sieve for later use; crush the carbide slag and fly ash and pass them through a 200-mesh sieve for later use. S2. Slurry preparation: Weigh 35% phosphogypsum, 21.67% carbide slag, and 43.33% fly ash, and dry mix them in a mixer for 10 minutes; weigh tap water and add it to the dry mixture according to a water-ash mass ratio of 0.49:1, stir it in a cement mortar mixer at 140 rpm for 3 minutes, let it stand for 90 seconds, and obtain a uniform slurry. S3, Compaction and Molding Stage: Pour the slurry from step S2 into a 40mm×40mm×160mm cement mortar soft mold, compact it on a cement vibration table, vibrate it 6 times, each time for 60s±2s, and demold it after standing for 24 hours. S4, High Humidity Pre-curing Stage: The sample compacted in step S3 is pre-cured for 24 hours at 20℃ and 98% relative humidity. S5. Carbonization curing: The samples after high humidity pre-curing in step S4 were placed in an air atmosphere of 20±2℃, 65% relative humidity, and 20% CO2 for carbonization curing for 3d, 7d, 14d and 28d. Comparative Example 1: The method is the same as in Example 1, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0016] Example 2: In this example, the phosphogypsum is 40%, the calcium carbide slag is 20%, and the fly ash is 40%. The rest of the preparation process and curing conditions are the same as in Example 1. Comparative Example 2: The method is the same as in Example 2, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0017] Example 3: In this example, the phosphogypsum content is 45%, the calcium carbide slag content is 18.33%, and the fly ash content is 36.67%. The remaining preparation process and curing conditions are the same as in Example 1. Comparative Example 3: The method is the same as in Example 3, except that after demolding, it is cured at 20℃ and 98% relative humidity for 28 days.
[0018] Example 4: In this example, the phosphogypsum content is 50%, the calcium carbide slag content is 16.67%, and the fly ash content is 33.33%. The remaining preparation process and curing conditions are the same as in Example 1. Comparative Example 4: The method is the same as in Example 4, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days. Example 5: In this example, the phosphogypsum is 55%, the calcium carbide slag is 15%, and the fly ash is 30%. The rest of the preparation process and curing conditions are the same as in Example 1. Comparative Example 5: The method is the same as in Example 5, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0019] Example 6: This example contains 60% phosphogypsum, 13.33% carbide slag, and 26.67% fly ash. The remaining preparation process and curing conditions are the same as in Example 1. Comparative Example 6: The method is the same as in Example 6, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0020] Example 7: In this example, the phosphogypsum content is 65%, the calcium carbide slag content is 11.67%, and the fly ash content is 23.33%. The remaining preparation process and curing conditions are the same as in Example 1. Comparative Example 7: The method is the same as in Example 7, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0021] Comparative Example 8: The method is the same as in Example 1, except that no phosphogypsum is added, only 33.33% carbide slag and 66.67% fly ash are added. The rest of the preparation process and curing conditions are the same as in Example 1.
[0022] Comparative Example 9: The method is the same as in Example 8, except that after demolding, it is cured at 20°C and 98% relative humidity for 28 days.
[0023] Example 8: Flexural and compressive strength tests of the materials prepared in Examples 1-7 and Comparative Examples 1-9 The methods are shown in Table 1, and the results are shown in Table 2. Figure 1-3 ; Figure 1 Compared with standard maintenance ( Figure 1b, Comparative Examples 1-7) and CO2 mineralization maintenance ( Figure 1 a) Under the conditions of Examples 1-7, the evolution of flexural strength of samples with different phosphogypsum (PG) contents (35%~65%) at 3d, 7d, 14d, and 28d curing times was investigated. The results showed that the flexural strength of the samples after CO2 mineralization curing was significantly higher than that of the corresponding standard-cured samples, confirming that mineralization curing can effectively improve the material's resistance to flexural failure. Taking the sample with a PG content of 35% as an example ( Figure 1 a) The flexural strengths after carbonization for 3d, 7d, 14d, and 28d were 0.475MPa, 0.72MPa, 0.76MPa, and 0.82MPa, respectively, which were significantly stronger than those of the same dosage sample under standard curing. Figure 1 b: Flexural strength (0.062 MPa, 0.083 MPa, 0.47 MPa, 0.65 MPa). In terms of growth trend, the growth is faster in the early stage of carbonization (0-7 days), and then the growth tends to slow down, indicating that the mineralization reaction mainly occurs in the early stage of curing.
[0024] Furthermore, under different PG dosage conditions, the flexural strength showed a trend of first increasing and then decreasing. Example 2 (PG dosage 40%) exhibited the best overall performance, with flexural strengths at each age reaching 0.675 MPa (3d), 0.715 MPa (7d), 0.76 MPa (14d), and 0.875 MPa (28d), respectively. However, when the PG dosage exceeded 40%, taking 65% dosage as an example, the flexural strengths at carbonization 3d-28d reached 0.22 MPa, 0.25 MPa, 0.28 MPa, and 0.32 MPa, respectively. The reason for this is that high phosphogypsum dosage diluted the relative proportions of carbide slag and fly ash in the system, leading to a reduction in active Ca, Si, and Al components, and a decrease in the formation of mineralization and cementation products, thus weakening strength development. These results indicate that CO2 mineralization curing can effectively compensate for the early strength loss caused by PG incorporation, allowing the material to maintain excellent mechanical properties while utilizing large quantities of solid waste.
[0025] Figure 3 Further comparison was made of the flexural strength of the control group without PG. The 28-day flexural strength of Control Example 8 (standard curing) was 0.70 MPa, while that of Control Example 9 (CO2 mineralization curing) increased to 1.00 MPa. This indicates that the introduction of CO2 promoted the transformation of hydration products and the deposition of calcium carbonate in the pores, enhancing the structural integrity of the material. In summary, this invention effectively strengthens the internal bonding effect of the material and significantly improves its crack resistance and flexural strength through the synergistic effect of high-humidity pre-curing and CO2 mineralization curing.
[0026] Compressive strength test results ( Figure 2The results show that after CO2 mineralization curing, the compressive strength of the samples in each example was significantly higher than that of the corresponding standard-cured samples, and continued to increase with the extension of carbonization age. Taking the example with 35% PG content as an example (…), Figure 2 a) The compressive strengths at 3d, 7d, 14d, and 28d after carbonization reached 5.8 MPa, 7.6 MPa, 8.75 MPa, and 9.2 MPa, respectively, which were significantly higher than those of the standard-cured samples with the same dosage (0.86 MPa, 1.3 MPa, 5.7 MPa, and 8.1 MPa), confirming the promoting effect of mineralization on early strength development. However, the compressive strength showed a significant decreasing trend with increasing PG dosage. When the PG dosage increased to 65%, the compressive strength at each carbonization age decreased to 1.8 MPa (3d), 2.4 MPa (7d), 2.6 MPa (14d), and 3.1 MPa (28d), respectively. This degradation was due to the dilution of the effective ratio of carbide slag and fly ash by excessive PG, resulting in a reduction of active components that could participate in alkali activation and carbonization reactions, inhibiting hydration activity, and reducing the amount of cementitious and mineralized products generated. Further comparison with the control group without PG ( Figure 3 (b) The 28-day compressive strength of Comparative Example 8 (traditional carbide slag-fly ash system, standard curing) was approximately 4 MPa, while that of Comparative Example 9 (traditional system, CO2 mineralization curing) increased to 6 MPa, indicating that carbonization curing also has a strengthening effect on the traditional system. Notably, the 28-day compressive strength of Example 1 (35% PG + CO2 mineralization curing) reached 9.2 MPa, significantly higher than both control groups and the highest among all examples. Analysis suggests that during mineralization curing, CO2 reacts with Ca(OH)2 and active calcium sources in the system to generate CaCO3, and simultaneously forms a continuous cementing network with C-(A)-SH and other cementing products, resulting in tighter interparticle bonding and significantly improved material load-bearing capacity. The results indicate that the formulation described in this invention can balance high utilization of solid waste with high mechanical load-bearing performance.
[0027] Example 9: Permeability test of materials prepared in Examples 1-7 and Comparative Examples 1-9 The methods are shown in Table 1, and the results are shown in Table 2. Figure 4-7 ; The results showed that after CO2 mineralization curing, the permeability coefficients of the materials in each example were significantly lower than those of the corresponding standard-cured samples, and continued to decrease with the extension of carbonization age. Specifically, the permeability coefficient of Example 1 (35% phosphogypsum) was 7.0 × 10⁻⁶ on day 3. - 6 cm / s, 3.2 × 10 on day 7. -6 cm / s, and 8.2 × 10 cm / s on day 14. -7 cm / s, 1.75 × 10 on day 28. -8cm / s; The permeability coefficient on day 3 in Example 2 (phosphogypsum 40%) was 7.8 × 10⁻⁶. -6 cm / s, 1.3 × 10 on day 7. -6 cm / s, and 1.94 × 10 on day 14. -7 cm / s, 2×10 on day 28 -8 cm / s; In Example 7 (65% phosphogypsum), the permeability coefficient on day 3 was 3 × 10⁻⁶. -4 cm / s, and 1.1 × 10 on day 7. -4 cm / s, 2.7 × 10 on day 14. -5 cm / s, 2.8 × 10 on day 28. -6 The permeability coefficient decreased most rapidly during carbonization from 3 to 7 days, then gradually slowed down, stabilizing after 28 days, indicating a stable mineralization reaction. Under different phosphogypsum dosages, Example 2 exhibited the best impermeability resistance, with the permeability coefficient decreasing to 7.30 × 10⁻⁶ after 28 days. -8 cm / s, lower than the 1.0×10 cm / s typically required for seepage prevention projects in mines. -7 The flow rate (cm / s) meets the seepage prevention requirements of the structural layer in mine ecological restoration. Analysis suggests that high-humidity pre-curing forms a continuous hydration framework, and subsequently, the large amount of CaCO3 generated by CO2 mineralization, along with cementing products, fills the pores and microcracks, reducing pore connectivity and effectively blocking water migration paths, thus giving the material excellent impermeability.
[0028] Figure 8 The permeability coefficient changes under two curing conditions (in the traditional carbide slag-fly ash system) were further compared, providing a contrast to the impermeability performance of Examples 1-7.
[0029] The osmotic coefficient of the traditional control group under standard curing conditions was 1.49 × 10⁻⁶ after 3 days. -5 cm / s, decreased to 3.82×10 after 7 days. -6 cm / s, 3.3 × 10⁻⁶ d. -7 cm / s, further decreased to 3.1 × 10 cm / s after 28 days. -7 cm / s ( Figure 8 b) Under carbonization curing conditions, the value after 3 days is 1.28 × 10⁻⁶. -5 cm / s, 5.41 × 10⁻⁶ d. -6 cm / s, 3.89 × 10⁻⁶ d. -7 cm / s, 28 days is 2.9×10 -8 Compared with the data of the example, the permeability coefficient of Example 2 (40% phosphogypsum) was as low as 2×10 cm / s after carbonization for 28 days. -8cm / s, which is far lower than the corresponding system under standard curing (Example 2, standard curing for 28 days, approximately 8.7 × 10 cm / s). -8 The speed (cm / s) was also lower than the 2.9 × 10⁻⁶ of the traditional control group after 28 days of carbonization. -8 cm / s, while meeting the standards for mine seepage prevention projects (≤1.0×10 cm / s). -7 (cm / s). This result indicates that although the absolute strength of the phosphogypsum-infused system is inferior to that of the traditional phosphogypsum-free system, in terms of impermeability, an appropriate amount (especially 40%) of phosphogypsum, after carbonization curing, is superior to the traditional control. Mechanistically, the SO4 provided by phosphogypsum... 2- The formation of ettringite (AFt) was promoted, forming a synergistic filling effect with the CaCO3 generated by carbonization: ettringite filled the micropores, while CaCO3 filled the larger pore throats. Together, they reduced pore connectivity, resulting in superior impermeability of the material. Although the traditional control group had a higher CSH formation, its pore filling efficiency was not as good as the precise sealing of the "bottleneck pores" by the ettringite-CaCO3 dual-phase system.
[0030] Figure 9 The infrared spectroscopy (FTIR) and X-ray diffraction (XRD) microstructure characterization results of the materials in Examples 2-4 and Comparative Examples 2-4 are presented. Figure 9 Infrared spectroscopy revealed that, regardless of the phosphogypsum content, the carbonized matrix exhibited similar water retention in the early stages. However, compared to the standard-cured control, Examples 2-4 showed different water retention at 3550 cm⁻¹. -1 The OH stretching vibration peaks in the vicinity were significantly weakened, which proves that CO2 mineralization caused a severe consumption of free Ca(OH)2 produced by hydration; at the same time, the 1450 cm⁻¹ peak was significantly weakened. -1 and 886cm -1 The nearby CO characteristic absorption peaks are significantly enhanced, directly reflecting the formation of carbonization products. Figure 9 The bXRD pattern further confirms that the significant impact of carbonation on the matrix is mainly reflected in the surge of the carbonate characteristic peak (Calcite). During carbonation, a large number of CaCO3 crystals are deposited in the pores and microcracks of the material, producing a synergistic micro-aggregate filling effect with cementitious products such as C-(A)-SH, blocking the water seepage channels, thus resulting in an extremely low permeability coefficient. When the phosphogypsum content is further increased (as in Example 7), the amount of carbonation products generated decreases slightly due to the relatively reduced proportion of calcium-rich and silicon-aluminum-rich active components such as carbide slag and fly ash in the system, and the increase in impermeability slows down accordingly. However, the overall density is still significantly better than the uncarbonized control.
[0031] Example 10: Leaching toxicity test of materials obtained in Examples 1-7 The methods are shown in Table 1, and the results are shown in Table 2; The results showed that the leaching concentrations of phosphorus and fluorine in all embodiments met the relevant standard requirements. Specifically, the phosphorus leaching concentration remained consistently below the limit specified in GB 11893-89 (≤0.2 mg / L), indicating that phosphorus could be stably solidified within the material system. With prolonged curing time, the fluoride ion leaching concentration continuously decreased, indicating that CO2 mineralization and gelation reactions continued, and the generated CaCO3 and gelation products jointly encapsulated and fixed soluble fluorides, reducing the migration capacity of pollutants. Even when the phosphogypsum content reached 65%, the leaching concentrations in all embodiments still met the standard requirements, indicating that the material of this invention has good environmental stability and can meet the application requirements of structural layer materials for mine ecological restoration. Based on the above research results, this invention, using a synergistic system of phosphogypsum, carbide slag, and fly ash, and combining high-humidity pre-curing with CO2 mineralization curing, can significantly improve the mechanical properties and impermeability of the material, while effectively reducing the leaching concentrations of pollutants such as phosphorus and fluorine, achieving the synergistic goal of resource utilization of industrial solid waste and CO2 mineralization and sequestration. Therefore, it is suitable for the preparation of structural layer materials for mine ecological restoration.
[0032] Based on the above research, this invention conducted an environmental risk analysis on the materials of Examples 1-7 and tested the P and F leaching of the materials. The results are shown in Table 2. The results show that the materials prepared by the method of this invention have very low leaching toxicity and meet the standard requirements. Therefore, the materials prepared by the method of this invention can be used as structural layer materials for mine ecological restoration. .
Claims
1. A method for preparing a structural layer material for mine ecological restoration using phosphogypsum and co-capture carbon, characterized in that: Phosphogypsum powder is mixed with crushed fly ash and carbide slag. After the mixture is aged at room temperature for 7-9 hours, water is added to the mixture to make a slurry. After pressing and molding, the slurry is pre-cured at 18-22℃ and relative humidity ≥95% for 24 hours, and then mineralized at 18-22℃, relative humidity 55-65%, and carbon dioxide atmosphere for more than 7 days to obtain the structural layer material for mine ecological restoration.
2. The method for preparing mine ecological restoration structural layer materials by phosphogypsum co-capture as described in claim 1, characterized in that: The raw materials are 35%–65% phosphogypsum, 11%–22% carbide slag, and 23%–40% fly ash by mass, with the mass ratio of carbide slag to fly ash being 1:
2.
3. The method for preparing mine ecological restoration structural layer materials by phosphogypsum co-capture as described in claim 1, characterized in that: The volume percentage of carbon dioxide in the carbon dioxide atmosphere is 20%.
4. The method for preparing mine ecological restoration structural layer materials by phosphogypsum co-capture as described in claim 1, characterized in that: The weight percentage content of CaSO4·2H2O in phosphogypsum is ≥80%.
5. The method for preparing mine ecological restoration structural layer materials by phosphogypsum co-capture as described in claim 1, characterized in that: The particle size of the crushed fly ash and carbide slag is less than 200 mesh.
6. The method for preparing mine ecological restoration structural layer materials by phosphogypsum co-capture as described in claim 1, characterized in that: Mixing is done by dry mixing in a mixer for 5-15 minutes.
7. The mine ecological restoration structural layer material prepared by the method according to any one of claims 1 to 6, characterized in that: The permeability coefficient of the material after 28 days is no greater than 1.0 × 10⁻⁶. -7 It has a speed of cm / s and also has pollutant barrier properties.
8. The application of the mine ecological restoration structural layer material according to claim 7 in mine ecological restoration engineering, characterized in that: Used for mine slope repair, tailings dam seepage prevention, abandoned mine pit remediation, contaminated site barrier layer or other mine ecological restoration projects.
Citation Information
Patent Citations
Intelligent manufacturing system
CN111133395A
Method for geological storage of carbon dioxide by using ardealite as filling material
CN115215624A